From Genotype to Phenotype: Nonsense Variants in SLC13A1 Are Associated with Decreased Serum Sulfate and Increased Serum Aminotransferases. Issue 9 (1st September 2016) - Tise, Christina G; Perry, James A; Anforth, Leslie E; Pavlovich, Mary A; Backman, Joshua D; Ryan, Kathleen A; Lewis, Joshua P; O'Connell, Jeffrey R; Yerges-Armstrong, Laura M; Shuldiner, Alan R
Abstract: Using genomic applications to glean insights into human biology, we systematically searched for nonsense single nucleotide variants (SNVs) that are rare in the general population but enriched in the Old Order Amish (Amish) due to founder effect. We identified two nonlinked, nonsense SNVs (R12X and W48X) in SLC13A1 (allele frequencies 0.29% and 0.74% in the Amish; enriched 1.2-fold and 3.7-fold, compared to the outbred Caucasian population, respectively). SLC13A1 encodes the apical sodium-sulfate cotransporter (NaS1) responsible for sulfate (re)absorption in the kidneys and intestine. SLC13A1 R12X and W48X were independently associated with a 27.6% ( P = 2.7 × 10 −8 ) and 27.3% ( P = 6.9 × 10 −14 ) decrease in serum sulfate, respectively ( P = 8.8 × 10 -20 for carriers of either SLC13A1 nonsense SNV). We further performed the first exome- and genome-wide association study (ExWAS/GWAS) of serum sulfate and identified a missense variant (L348P) in SLC26A1, which encodes the basolateral sulfate-anion transporter (Sat1), that was associated with decreased serum sulfate ( P = 4.4 × 10 −12 ). Consistent with sulfate's role in xenobiotic detoxification and protection against acetaminophen-induced hepatotoxicity, SLC13A1 nonsense SNV carriers had higher aminotransferase levels compared to noncarriers. Furthermore, SLC26A1 L348P was associated with lower whole-body bone mineral density (BMD) and higher serum calcium, consistent with the osteochondrodysplasia exhibited by dogs and sheep with naturally occurring, homozygous, loss-of-function mutations in Slc13a1 . This study demonstrates the power and translational potential of systematic identification and characterization of rare, loss-of-function variants and warrants additional studies to better understand the importance of sulfate in human physiology, disease, and drug toxicity.